2023
DOI: 10.1177/13591045231200661
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle habits, health indicators and sociodemographic factors associated with health-related quality of life and self-esteem in adolescents

Raúl Jiménez Boraita,
Esther Gargallo Ibort,
Josep María Dalmau Torres
et al.

Abstract: Background Mental health is defined as a state of emotional, psychological, and social well-being, and has been shown to be positively associated with self-esteem and quality of life. It is important to note that mental health is dynamic and influenced by a wide range of social, biological, and behavioral factors. Therefore, the aim this study was to describe the health-related quality of life and self-esteem in adolescents, examining their relationship with various health indicators, lifestyle habits, and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…For instance, Smith et al (2023) conducted a study with 302 adolescent participants and found that teenagers with attention deficit or hyperactivity disorders generally exhibit lower levels of learning motivation, which in turn affects their academic performance. The internal factors such as sleep (Boraita et al, 2023;Chan et al, 2023;Hamvai et al, 2023), depression (Song et al, 2023;Urbanska-Grosz et al, 2023), and disordered social media use (Almarzouki et al, 2022;Sserunkuuma et al, 2023) also exert varying degrees of influence on academic performance. In this study, we primarily investigate the internal factors pertaining to learning state, encompassing self-efficacy and learning behavior.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Smith et al (2023) conducted a study with 302 adolescent participants and found that teenagers with attention deficit or hyperactivity disorders generally exhibit lower levels of learning motivation, which in turn affects their academic performance. The internal factors such as sleep (Boraita et al, 2023;Chan et al, 2023;Hamvai et al, 2023), depression (Song et al, 2023;Urbanska-Grosz et al, 2023), and disordered social media use (Almarzouki et al, 2022;Sserunkuuma et al, 2023) also exert varying degrees of influence on academic performance. In this study, we primarily investigate the internal factors pertaining to learning state, encompassing self-efficacy and learning behavior.…”
Section: Introductionmentioning
confidence: 99%